1996
DOI: 10.1073/pnas.93.13.6437
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of the immunity protein of colicin E7 suggests a possible colicin-interacting surface.

Abstract: The immunity protein of colicin E7 (ImmE7) can bind specifically to the DNase-type colicin E7 and inhibit its bactericidal activity. Here we report the 1.8-A crystal structure of the ImmE7 protein. This is the first x-ray structure determined in the superfamily of colicin immunity proteins. The ImmE7 protein consists of four antiparallel ci-helices, folded in a topology similar to the architecture of a four-helix bundle structure. A region rich in acidic residues is identified. This negatively charged area has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 25 publications
2
51
3
Order By: Relevance
“…Notably, neither H40 nor H47 exhibit the 4:1 ratio in the native conformation of the protein, with H40 predominantly in the rare δ tautomer form and H47 exclusively in the « state, suggesting that both histidines are in hydrogen-bonded environments. Indeed, crystal structures of Im7 show that H47 stacks on W75 and is hydrogen bonded to the backbone amide of D49, whereas H40 becomes buried by the N terminus in the native state, potentially forming a hydrogen bond with the backbone carbonyl of K4 (77,78). Thus, significant rearrangements of the histidine side chains must accompany the I-to-N transition, leading to burial of the exposed H40 and H47 side chains.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, neither H40 nor H47 exhibit the 4:1 ratio in the native conformation of the protein, with H40 predominantly in the rare δ tautomer form and H47 exclusively in the « state, suggesting that both histidines are in hydrogen-bonded environments. Indeed, crystal structures of Im7 show that H47 stacks on W75 and is hydrogen bonded to the backbone amide of D49, whereas H40 becomes buried by the N terminus in the native state, potentially forming a hydrogen bond with the backbone carbonyl of K4 (77,78). Thus, significant rearrangements of the histidine side chains must accompany the I-to-N transition, leading to burial of the exposed H40 and H47 side chains.…”
Section: Discussionmentioning
confidence: 99%
“…In order to exert cell killing activity, ColE7 has to get across both the outer and the inner cell membrane, facilitated by the receptor-binding and translocation domains [3,4]. The host cell itself is protected by the simultaneously expressed immunity protein Im7 blocking the DNA-binding site [5,6] of the NColE7 domain due to tight interactions based on charge-complementarity [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…1). The E7 DNaseIm7 complex was expressed as a histidine-tagged complex (in which the Im7 protein carried the tag) and the structure solved by molecular replacement using the previously solved Im7 crystal structure (22,26). Atomic absorption experiments indicated that zinc was the predominant metal in this complex, although nickel could also be detected (22).…”
mentioning
confidence: 99%